THE IMPORTANCE AND FEATURES OF TEACHING STUDENTS MOTHER LANGUAGE (American Journal of Pedagogical and Educational Research, 2024)
Language is a fundamental aspect of human communication and identity. Teaching students their mother tongue plays a crucial role in cognitive development, cultural preservation, and academic success. This article explores the importance of mother tongue teaching and highlights the key features that contribute to effective language learning outcomes.